السفر الطويل وأثره على حقوق الزوجين : دراسة فقهية تحليلية - حسين، عبد الواسع
This research aims to study an important issue of long travel and its impact on the rights of spouses. The research has attracted much attention at present due to the circumstances that have forced many people to travel long for a variety of reasons. This study explains the travel of one of the spouses and its impact on their rights and their children’s rights and the legal rulings that it entails. The researcher relied on the inductive method to trace the scientific particles from the texts of the purified Sharia and the opinions of the jurists. The analytical method was employed to analyse the opinions, sayings, and scientific research related to the topic. The researcher reached several results, the most important of which are: the rights of the husband, the rights of the wife, the common rights between them, and the rights of their children are the effects of a legal marriage. Legal marriage has original purposes, such as chastity, preserving lineages, and training children. It also has subsidiary purposes such as preserving the human race, creating a cohesive and happy family, immunizing spouses, and protecting women from humiliation. The long travel is one of the modern and current events where the Sharia has laid out specific purposes and goals. Moreover, the Islamic jurists have worked hard to establish legal methods for the long absence and its important reasons, whether physical or spiritual and that the separation of one of the spouses is a reason affecting some important rights of children, such as custody, supervision, training, and education. Many scholars insisted on the condition of Mahram for a female traveller to preserve her religion and honour. Modernity does not affect the prohibition of a woman traveling without a Mahram for fear of women exists in every time and place. The researcher most important recommendations are: the necessity of the original and subordination purposes of marriage which Islam prescribes, and to make every effort to fulfil the rights, whether those rights were material, moral, social, or economic, living in one’s dwelling and taking care of the family in particular, and try not to stay for long. Adherence to the important Sharia regulations is imperative in shaping one’s Islamic life.